Orexin-A Exerts Neuroprotective Effects via OX1R in Parkinson’s Disease - Liu, Mei-Fang; Xue, Yan; Liu, Cui; Liu, Yun-Hai; Diao, Hui-Ling; Wang, Ying; Pan, Yi-Peng; Chen, Lei (Frontiers in Neuroscience, 2018)
Parkinson’s disease (PD) is a common neurodegenerative disorder characterized by progressive and selective death of dopaminergic neurons. Orexin-A is involved in many biological effects of the body. It has been reported that orexin-A has protective effects in cellular models of PD. However, little is known about the protective effects of orexin-A in animal parkinsonian models and the cellular mechanism has not yet been fully clarified. The aim of this study was to evaluate the effects of orexin-A in MPTP mice model of PD as well as the possible neuroprotective mechanisms of orexin-A on dopaminergic neurons. The results from animal experiments demonstrated that orexin-A attenuated the loss of dopaminergic neurons and the decrease of tyrosine hydroxylase (TH) expression in the substantia nigra, normalized the striatal dopaminergic fibers, and prevented the depletion of dopamine and its metabolites in the striatum. MPTP-treated mice showed cognitive impairments accompanied with significant motor deficiency. Orexin-A improved MPTP-induced impairments in both motor activity and spatial memory. Importantly, orexin-A increased the protein level of brain-derived neurotrophic factor (BDNF) in dopaminergic neurons of the substantia nigra. Furthermore, the protective effects of orexin-A on MPTP parkinsonian mice could be blocked by orexinergic receptor 1 (OX1R) antagonist, SB334867. In another set of experiments with SH-SY5Y dopaminergic cells, orexin-A significantly induced the expression of BDNF in a dose and time-dependent manner. The upregulation of BDNF is mainly concerned with PI3K and PKC signaling pathways via OX1R. The present study demonstrated that orexin-A exerted neuroprotective effects on MPTP parkinsonian mice, which may imply orexin-A as a potential therapeutic target for PD.